Wind-driven coastal circulation in the Gulf of Tehuantepec, Mexico - FA Velázquez-Muñoz; JA Martínez; C Chavanne; R Durazo; P Flament (Ciencias Marinas, 2011)
Sea surface current measurements and wind stress and sea surface temperature satellite data were used to study the effect of northerly wind events (Tehuanos) on coastal dynamics in the Gulf of Tehuantepec, Mexico. The winter 2005 observations show a significant change in the intensity and direction of surface currents during wind events, which is reflected in an increase in kinetic energy and negative relative vorticity. The analysis revealed that kinetic energy of the coastal current decreases (increases) in periods when there is absence (presence) of Tehuano wind events, and that the relative vorticity has a tendency to positive values under low wind conditions and a tendency to negative values during high wind events. An asymmetric ocean response was observed due to wind stress forcing and the interaction between a persistent coastal current and offshore wind stress. Con base en mediciones de corrientes superficiales del océano e información satelital de vientos y temperatura superficial del océano, se estudió el efecto de los eventos de viento del norte (tehuanos) sobre la dinámica costera en el golfo de Tehuantepec, México. Las observaciones realizadas durante el invierno de 2005 mostraron un cambio significativo en la intensidad y dirección de las corrientes superficiales durante los eventos de viento, que se vio reflejado en un aumento de la energía cinética y de la vorticidad relativa negativa. El análisis mostró que la energía cinética de la corriente costera decrece (incrementa) en los periodos cuando hay ausencia (presencia) de eventos de viento tehuano, y que la vorticidad relativa presenta una tendencia a valores positivos bajo condiciones de viento débil y una notoria tendencia a valores negativos durante los eventos de viento intenso. Se observó una asimetría en la respuesta del océano por el forzamiento del esfuerzo del viento y la interacción entre una corriente costera persistente y el viento normal a la costa.